A case of squamous cell lung cancer treated with anamorelin in combination with a multidisciplinary collaborative approach for treating cancer cachexia. (2022) - Oshima, Yuri; Matsuura, Hiroyuki; Sakurai, Yusuke; Hirai, Kaho; Tani, Eriko; Yoshimoto, Naoki; Minami, Kenichi; Yamasaki, Fumio; Nishime, Mayu; Hirashima, Tomonori
Abstract: Anamorelin (ANA) is approved for treating cancer cachexia (CCX) in Japan. We report the case of a 69-year-old man with stage IVB squamous cell lung cancer complicated by CCX, having a 13.6% weight loss in 6 months. After chemotherapy was initiated, his weight was further reduced. Therefore, we started ANA combined with a treatment approach by a multidisciplinary collaboration, including nutritionists and physical therapists. After initiation of ANA, the body weight, appetite, psoas muscle index, and physical functions rapidly improved during chemotherapy. ANA administration combined with a multidisciplinary collaboration approach can be an effective supportive therapy against CCX during chemotherapy.